Comparative study of chemical composition at different stages of growth, green fodder intake and green fodder yield of DHN-6 and CO-4 green fodder - PATIL, P V; SALUNKE, V M; DEVKATE, P P (The Indian Journal of Animal Sciences, 2021)
The present study was conducted with the objective to evaluate the usefulness of DHN-6 and CO-4 fodders in terms of chemical composition, fodder intake and other parameters. The green fodder samples of both fodders were collected on 10, 20, 30, 40, 50, 60, 70 and 80 days of plantation and chemical composition was analysed accordingly. Green fodder intake of DHN-6 and CO-4 was recorded for 20 days in Deoni cows. Moisture level in chaffed fodder was evaluated upto 9 h of chaffing of green fodder. The chemical composition of DHN-6 fodder was found better than the CO-4 fodder. DHN-6 fodder has more juiciness, sweetness; high green fodder intake, high moisture-holding capacity and more green fodder yield as compared to CO-4 fodder variety whereas CO-4 green fodder was found easy for harvesting and chewing to animals. No difference was found in the greenishness of both of the fodders. Overall it can be concluded that DHN-6 fodder is superior for feeding to animals as compared to CO-4 fodder and harvesting of these grasses should be carried out at 50 to 70 days of plantation to provide better nutrition to animals.